Effectiveness of Transjugular Intrahepatic Portosystemic Shunt in Variceal Bleeding: An Audit from a Tertiary Care Center in North India - Gupta, Arun; Mehta, Ajay; Mishra, Nitin; Bansal, Rajendra; Yadav, Ajit (Journal of Clinical Interventional Radiology ISVIR, 2017)
Variceal bleeding is one of the most feared complications of cirrhosis and portal hypertension. Transjugular intrahepatic portosystemic shunt (TIPS) is an effective minimally invasive option to achieve adequate decompression of the portal system. The aim of the study was to assess the efficacy and complications of TIPS in patients presenting with variceal bleed. It was a retrospective study done in a tertiary care center in North India in cirrhotic patients with acute or recurrent variceal bleed who underwent TIPS from April 2010 to October 2013. All the patients were followed up till April 2014. We could successfully implant TIPS in 100% of our patients with 100% success rate in controlling variceal bleeding immediately and during the follow-up period. Our primary patency rate was 94.5% and overall patency rate was 100%. Major TIPS-related complication was hepatic encephalopathy in 20% of patients; 7 of 22 patients died during the follow-up period. TIPS is a safe and effective procedure for control of acute or recurrent variceal bleed. Emerging evidence in favor of early TIPS is further going to expand its indication in variceal bleed. Hepatic encephalopathy was the major procedure-related complication in our study consistent with previous literature reports.
Keywords: TIPS; variceal bleed; encephalopathy